Evaluation of Training Provision/Programs for Existing and Prospective School Headteachers in England - Şakir Çınkır (Anı Publishing, 2019)
This study aims to evalutae the views of school administrators on England school headteacher training programs, which can be an example for the training of school headteachers in Turkey. Based on these views, school headteachers' training programs are evaluated in terms of needs assessment, organizational arrangements, the effectiveness of educational activities, the content of programs, and effectiveness and benefits of Headteacher's Leadership and Management Program (HEADLAMP) and National Professional Qualification for Headship (NPQH). Given a lack of published evaluations of these programs, a knowledge-building, developmental investigation was designed and conducted into HEADLAMP and NPQH participants' views of the processes and impact of these programs. Based on the general tendencies of the participants, it was determined that they had positive opinions about the quality of school headteachers' training; however, a) deputy heads in particular expressed serious concern about the need for realistic support to engage in headship training whilst continuing to fulfil their existing posts; b) participants emphasised the importance of also including training provision situated within real school contexts; c) they emphasised the importance of quality of local implementation. In the context of other recent papers on these programs, recent alterations to them by the TTA and a critical reflection on the strengths and weaknesses of the present investigation, possible implications for the UK and Turkish situations were discussed.